Introduction to the Special Issue on Learning Analytics - Karen Swan (Online Learning, 2012)
We have passed from an industrial to an information age. One consequence of this move is the information overload envisioned by Vannevar Bush over a half century ago. The growth of data often seems to threaten the ability of organizations to make sense of it. However, the gargantuan amount of available data also has enabled the development of new techniques that have changed the very ways businesses are managed, doctors make diagnoses, and baseball managers recruit and coach players. Advances in knowledge modeling and representation, data mining, and analytics are creating a foundation for new models of knowledge development and analysis. Perhaps nowhere are these new models more needed than in education.